2022
DOI: 10.23990/sa.103415
|View full text |Cite
|
Sign up to set email alerts
|

Tukityöllistäminen interventiona ja sen vaikutus perusterveydenhuollon palvelujen käyttöön

Abstract: Pitkittynyt työttömyys voidaan katkaista lyhytkestoisella tukityöllistämisellä, jolla voi olla vaikutusta työttömien hyvinvointiin, terveyteen ja toimintakykyyn. Työllistäminen voi vaikuttaa myös perusterveydenhuollon avopalvelujen käyttöön esimerkiksi tuomalla näkyväksi piilevää palvelutarvetta. Artikkelissa tutkitaan harvaan asutun kunnan tukityöllistämistoimenpiteisiin osallistuneiden ja työllistämisen ulkopuolelle jääneiden perusterveydenhuollon avopalvelujen käyttöä viiden vuoden aikana (2 vuotta ennen ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the above-mentioned effect of not needing sickness absence certificates during unemployment may explain part of this result. Among the long-term unemployed, the health services have been found to be inadequate [ 12 ] and their use polarised: Some use services frequently, others do not use them at all [ 15 – 16 ]. Overall, the unemployed have a higher risk for unmet healthcare needs [ 29 , 30 ] compared to the employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the above-mentioned effect of not needing sickness absence certificates during unemployment may explain part of this result. Among the long-term unemployed, the health services have been found to be inadequate [ 12 ] and their use polarised: Some use services frequently, others do not use them at all [ 15 – 16 ]. Overall, the unemployed have a higher risk for unmet healthcare needs [ 29 , 30 ] compared to the employed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the unemployed use more healthcare services than the employed [9,10], while other studies have shown that the unemployed use less services [1,[11][12][13] or that the use of services is at a similar level [14] compared to employed persons. Furthermore, results concerning the associations with the duration of unemployment have been conflicting [12,15,16]. Previous studies have mostly examined the associations of unemployment with the use of healthcare services.…”
Section: Introductionmentioning
confidence: 99%